1977
DOI: 10.1159/000251069
|View full text |Cite
|
Sign up to set email alerts
|

The Retinoic Acid Derivative Ro 11-1430 in Acne vulgaris

Abstract: In a double-blind controlled multicenter trial consisting of 257 patients with acne vulgaris an 8-week topical treatment with the retinoic acid derivative Ro 11-1430 (0.1% lotion) was compared with vitamin A acid (0.05% lotion) and the lotion alone (placebo). In reducing the number of comedones vitamin A acid was superior to Ro 11-1430, which was significantly better than placebo. The reduction in number of papules and pustules was not statistically significant on either treatment. Local side effects, i.e. ery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The clinical effect of Ro 11-1430 on comedones is generally considered as lower compared to tretinoin as observed by Christiansen et al [4] and Braathen et a!. [2], A remarkable result in this study was the relative lack of a demonstrable effect on comedones even with tretinoin in a great number of the patients despite the long observation time.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The clinical effect of Ro 11-1430 on comedones is generally considered as lower compared to tretinoin as observed by Christiansen et al [4] and Braathen et a!. [2], A remarkable result in this study was the relative lack of a demonstrable effect on comedones even with tretinoin in a great number of the patients despite the long observation time.…”
Section: Discussionmentioning
confidence: 54%
“…However, significantly more side effects, such as erythema, desquamation and burning, occurred after treatment with tretinoin than with Ro 11-1430. In a double blind multicenter study of 257 patients with acne, Christiansen et al [4] found that tretinoin produced more frequent and more severe local side effects than Ro 11-1430, which did not produce more side effects than placebo. However, tretinoin was superior to Ro 11-1430 in reducing the number of comedones and Ro 11-1430 was significantly more effective than placebo in this respect.…”
mentioning
confidence: 99%
“…It is claimed to reduce numbers of comedones , but in some studies the results are little different from placebo (NORDIN et al 1981) and there is similar disagreement about the respone of inflamed lesions (CHRISTIANSEN et al 1977;NORDIN et al 1981). Unlike isotretinoin, it appears not to be sebostatic ) and does not reduce bacterial numbers.…”
Section: Tretinoin (Retinoic Acid)mentioning
confidence: 99%
“…The ther apeutic effects of topically applied 0.1 % mo tretinide and 0.05% retinoic acid on acne vulgaris have been found to be similar [Christiansen et al, 1976[Christiansen et al, , 1977Braathen et al 1978], Benzoyl peroxide administered topically has been shown to have a good therapeutic effect on acne vulgaris [Liddel, 1974;Jo hansson and Sulionen, 1978], However, lo cal side-effects in the form of skin irritation were noted in 41% of the patients in the stu dy, and this effect seemed to be a toxic and not an allergic reaction.…”
Section: Introductionmentioning
confidence: 95%